Inhaled nitric oxide and high concentrations of oxygen in pediatrics patients with congenital cardiopathy and pulmonary hypertension: report of five cases - Carvalho, Werther Brunow de (1998)
Five patients with ages ranging from 6 months to 3 years were analyzed. All received inhaled nitric oxide (NO - 20 parts per million (ppm) ) and oxygen (0(2) - at a concentration of 90-95%) by means of an oxygen hood. Mean Pulmonary Artery Pressure (MPAP), Mean Aortic Pressure (MAoP), Pulmonary Vascular Resistance (PVR) and Systemic Vascular Resistance (SVR) were measured and the calculation of their relationship to pulmonary/systemic flow (Qp/Qs) was performed by the catheterization' of the femoral artery vein. Three patients presented reduction in PVR and increase in Qp/Qs. There were no systemic alterations or any side effect from using NO.